2016
DOI: 10.1111/bjet.12528
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relevance of single‐gender group formation: What we learn from a massive open online course (MOOC)

Abstract: This paper reports the results of an exploratory study on participants' perception of the importance of single-gender grouping in a massive open online course (MOOC) delivered through the Coursera platform. Findings reveal that female and male learners' perception of single-gender grouping differs. Female students more than males indicated less preference for single-gender grouping. Views on single-gender grouping also differed across regions, suggesting the effect of participants' regions of origin on their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…Although it would be premature to conclude that males are inherently more engaged than females in the MOOC context, this observation sends a signal that gender is associated with engagement and should be considered when developing MOOCs. Future research could explore, for example, the effectiveness of single‐gender grouping in MOOCs that adopt group work and peer grading assessments (Bayeck, Hristova, Jablokow, & Bonafini, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although it would be premature to conclude that males are inherently more engaged than females in the MOOC context, this observation sends a signal that gender is associated with engagement and should be considered when developing MOOCs. Future research could explore, for example, the effectiveness of single‐gender grouping in MOOCs that adopt group work and peer grading assessments (Bayeck, Hristova, Jablokow, & Bonafini, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cisel (2014) indicated that learner performance in MOOCs was highly correlated with the learner's geographic location, employment status, and time constraints, and that unemployed learners from high Human Development Index (HDI) countries were more likely to complete the course. Other variables that have been examined for their effects on MOOC completion include years of education (Guo & Reinecke, 2014;Schulze, 2014), friends' performance in a MOOC (Brown et al, 2015), prior online learning experience (Morris, Hotchkiss, & Swinnerton, 2015), English proficiency (Engle, Mankoff, & Carbrey, 2015;Konstan, Walker, Brooks, Brown, & Ekstrand, 2015;Schulze, 2014), number of posts and number of videos watched (Bonafini, 2017;Bonafini, Chae, Park, & Jablokow, 2017), gender (Bayeck, Hristova, Jablokow, & Bonafini, 2018;Breslow et al, 2013;Konstan et al, 2015;Schulze, 2014), and age (Breslow et al, 2013;Guo & Reinecke, 2014;Konstan et al, 2015;Morris et al, 2015;Schulze, 2014;Zhang et al, 2016). Most of the studies agree that there is a positive relationship between age and MOOC completion rates.…”
Section: Introductionmentioning
confidence: 99%
“…The inspiration for the questionnaire is derived from Professor LI Yunhuo's LICC teaching mode. According to the twenty observational perspectives of four main elements, namely Learning, Instruction, Curriculum and Culture, so that the content of the questionnaire is more scientific (Bayeck, Hristova, Jablokow & Bonafini, 2016). The content of the questionnaire survey is mainly divided into four parts: statistical survey of students' basic information, survey of classroom teaching method and quality, student's classroom performance and students' suggestions for the teaching mode.…”
Section: Questionnaire Surveymentioning
confidence: 99%